Study on wear mechanism of gear pump end plate of combined harvester based on CFD fluid analysis. (31st May 2018) - Gao, Liqiang; Hu, Xiong; Liu, Wei; Sun, Dejian
Summary: Aiming at the floating end plate wear of the high pressure gear pump of combine harvester, the key factors that lead to overturning moment of the end plate and the dynamic equilibrium mechanism of the end plate were studied emphatically. The internal flow field of gear pump with a model of gear pump of a certain type combine harvester was analyzed using CFD software, and according to the characteristics of the end plate structure, the differential equation about the compression force and the anti – thrust was established, and the overturning moment change rules of the end plate in the meshing period of 1 wheel tooth can be obtained. Meanwhile, the experimental system was established to verify the theoretical analysis results. The experimental data show that the error of the overturning moment test and the theoretical value is 4.18% under rated condition and when the gear angle φ = 14°, the overturning moment reaches the maximum value M s = 82.16 N·m. The research provides theoretical basis and technical support for the structural optimization design to reduce the wear of end plates.